Original papersCorrelation between serum interleukin 31 level and the severity of disease in children with atopic dermatitis - Siniewicz-Luzeńczyk, Katarzyna; Stańczyk-Przyłuska, Anna; Zeman, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin disease, characterized by intense itch, typical localization and a specific image of skin lesions. Pathogenesis of pruritus in AD is not fully understood, but recent studies emphasize the role of interleukin-31 (IL-31). This relatively recently described cytokine is considered to be a potential mediator inducing pruritus in AD. Aim: To assess the correlation of serum IL-31 level and the disease severity in children with AD. Material and methods : Twenty-five children (16 girls and 9 boys) with AD aged from 4 months to 17 years (mean age: 4.2 years) were enrolled in the study. Disease severity in children with AD was assessed using the SCORAD (Severity SCORing of Atopic Dermatitis) index. Serum IL-31 levels were measured using ELISA with standard kits from EIAab R&D Systems. Results: Serum IL-31 level was significantly higher in AD children than in healthy children. There was no statistic correlation between serum IL-31 level and the disease severity or itch intensity. Conclusions : The disease severity and itch intensity do not correlate with serum IL-31 level in children with atopic dermatitis.